2019
DOI: 10.3390/ijms21010002
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Protein Prenylation of GTPases Alters Endothelial Barrier Function

Abstract: The members of Rho family of GTPases, RhoA and Rac1 regulate endothelial cytoskeleton dynamics and hence barrier integrity. The spatial activities of these GTPases are regulated by post-translational prenylation. In the present study, we investigated the effect of prenylation inhibition on the endothelial cytoskeleton and barrier properties. The study was carried out in human umbilical vein endothelial cells (HUVEC) and protein prenylation is manipulated with various pharmacological inhibitors. Inhibition of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Primary human umbilical vein endothelial cells (HUVECs) were isolated with collagenase IV as described previously by us [26]. The harvested cells were cultured in PromoCell ® endothelial cell basal medium supplemented with 10% (vol/vol) FCS, 0.4% (vol/vol) endothelial growth supplement with heparin, 0.1 ng/mL human EGF, 1.0 µg/mL hydrocortisone, 1 ng/mL human bFGF, and 2% (v/v) penicillin/streptomycin in humidified atmosphere at 37 • C, 5% CO 2 , and used at passage 1.…”
Section: Isolation Of Human Cardiomyocytes and Huvecsmentioning
confidence: 99%
“…Primary human umbilical vein endothelial cells (HUVECs) were isolated with collagenase IV as described previously by us [26]. The harvested cells were cultured in PromoCell ® endothelial cell basal medium supplemented with 10% (vol/vol) FCS, 0.4% (vol/vol) endothelial growth supplement with heparin, 0.1 ng/mL human EGF, 1.0 µg/mL hydrocortisone, 1 ng/mL human bFGF, and 2% (v/v) penicillin/streptomycin in humidified atmosphere at 37 • C, 5% CO 2 , and used at passage 1.…”
Section: Isolation Of Human Cardiomyocytes and Huvecsmentioning
confidence: 99%
“…The results of the GO enrichment analysis showed that the most significantly enriched GO term in the BF was organic substance metabolic process, the CC was intracellular, and in MF, binding. The GO enrichment analysis indicated that circRNA functions were highly associated with the metabolic process and GTPase, which have been shown to have a relationship with sepsis and endothelial barrier function in previous studies, respectively ( Mira et al, 2017 ; Aslam et al, 2019 ; Sanchez and Raja, 2022 ). The enrichment analysis of the KEGG pathway revealed that circRNAs were mainly involved in adherens junction, NF-kappa B signaling pathway, endocytosis, regulation of actin cytoskeleton, bacterial invasion of epithelial cells, antigen processing and presentation, and which also predicted that circRNAs might be related to endothelial barrier function in sepsis ( Garcia et al, 2018 ; McRae et al, 2018 ; Radeva and Waschke, 2018 ; Leonard et al, 2019 ; Strauss and Gourdie, 2020 ).…”
Section: Discussionmentioning
confidence: 75%
“…Moreover, newly synthesized Rho GTPases such as Rac1, Cdc42, or RhoA were shown to be rapidly prenylated in the cytosol and then transferred to the endoplasmic reticulum (ER) for further modifications [ 195 , 200 , 201 , 202 ]. Once attached to the membrane, specific GTPases carry out a variety of functions, from neurite outgrowth and guidance (Rac1) to inhibiting neuronal extensions and promoting growth cone collapse (RhoA) [ 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 ]. Importantly, transport of these proteins from the endoplasmic reticulum to the PM requires another modification which is palmitoylation.…”
Section: Post-translational Modifications Of Rho Gtpases Involved mentioning
confidence: 99%